BERJUANG MENYELAMATKAN LINGKUNGAN: GERAKAN LINGKUNGAN DI JAWA MASA KEMERDEKAAN 1950-2000 - Nawiyanto, Nawiyanto (Paramita: Historical Studies Journal, 2015)
This article discusses the environmental movement in Java during the independence era, with a special focus on the Old Order and New Order periods. Historical method was employed here in conducting the collection of source materials and synthesizing the facts into a historiographical construction. The sense of environmental crisis became the reason for continuing struggle for saving the environment. The result of discussion reveals that not only did it perform colonial legacy, the movement also resulted in modifications, in terms of conservation management and movement forms. There was also a process of strengthening and broadening of the supporting groups of the movement. Especially since the 1970s, the role of non-governmental organizations and media groups intensified. This feature marked a new era that ended the dominant role of the government. In line with this process, new environmental issues were also raised and pollution was a case in point here. Keywords: Environmental movement, environmental issues, government, non-governmental organizations, independence era, JavaArtikel ini membahas gerakan lingkungan di Jawa pada masa kemerdekaan dengan fokus khusus periode Orde Lama dan Orde Baru. Metode sejarah digunakan dalam penggarapan dari pengumpulan sumber hingga penuangan dalam sintesis konstruksi historiografis. Keyakinan akan krisis lingkungan menjadi alasan berlanjutnya perjuangan menyelamatkan lingkungan. Hasil pembahasan menunjukkan bahwa tidak hanya warisan kolonial tetap hidup, gerakan lingkungan memperlihatkan pula adanya modifikasi dalam hal pengelolaan kawasan konservasi dan bentuk gerakan. Terdapat pula proses penguatan dan perluasan kelompok-kelompok pendukung gerakan. Khususnya sejak tahun 1970-an, peranan organisasi non-pemerintah, media massa, dan kelompok-kelompok akar rumput semakin     menguat. Hal ini menandai sebuah era baru yang mengakhiri peranan dominan pemerintah. Seiring dengan proses ini, isu-isu baru juga dibangun dan pencemaran merupakan ilustrasi pokok di sini.  Kata kunci: gerakan lingkungan, isu lingkungan, pemerintah, organisasi non-pemerintah, masa kemerdekaan, Jawa